2013
DOI: 10.1021/jo400454e
|View full text |Cite
|
Sign up to set email alerts
|

α-Monoacylated and α,α′- and α,β′-Diacylated Dipyrrins as Highly Sensitive Fluorescence “Turn-on” Zn2+ Probes

Abstract: With the purpose of developing readily synthesized CHEF (chelation-enhanced fluorescence) type Zn(2+) probes with relatively simple molecular structures and excellent sensing behavior, p-anisoyl chloride was used for the acylation of 5-(pentafluorophenyl)dipyrromethane. Interestingly, the α,β'-diacylated product PS2 with a unique substitution mode was obtained in high yield in addition to the normal α-substituted mono- and diacylated products PS1 and PS3. Further oxidation of PS1-PS3 afforded dipyrrins S1-S3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(43 citation statements)
references
References 116 publications
1
40
0
2
Order By: Relevance
“…The fairly large Stokes shifts of all dipyrrins in the range of 2000–2700 cm −1 make these compounds interesting for many applications . To our surprise, only a few studies on the fluorescence of dipyrrins are reported …”
Section: Resultsmentioning
confidence: 99%
“…The fairly large Stokes shifts of all dipyrrins in the range of 2000–2700 cm −1 make these compounds interesting for many applications . To our surprise, only a few studies on the fluorescence of dipyrrins are reported …”
Section: Resultsmentioning
confidence: 99%
“…[26] Therefore, an accurate and reliable method for the determination of chromium ions is important. The detection of chromium ions in water samples has been performed by a variety of techniques, including electrothermal atomic absorption spectrometry, [27,28] atomic absorption spectrometry, [29] fluorescence spectroscopy, [30][31][32] potentiometric membrane sensing, [33] and electrolysis. [34] Among the many detection methods, colorimetric detection based on gold nanoparticles is particularly attractive for point-of-use applications owing to its low cost, speed, and especially ease of readout (even with the naked eye).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent data analysis revealed an excellent linear relationship (R = 0.999) between the relative fluorescence intensity at 502 nm and the Hcy concentration (0-30 mol/L). The detection limit for Hcy, based on the definition by IUPAC (CDL = 3 Sb/m) [54][55][56][57][58][59], was calculated to be 0.017 mol/L. Similarly, the detection limits for Cys and GSH were evaluated to be 0.043 mol/L and 0.053 mol/L, respectively (Fig.…”
Section: Fluorescence Spectra Titration For Thiolsmentioning
confidence: 99%